PERAN SOE HOK GIE DIDALAM PERJUANGAN MAHASISWA ANGKATAN 66 MELAWAN KEKUASAAN PEMERINTAHAN ORDE BARU - Leonardus Bagus Setiadi; Kuswono Kuswono (Swarnadwipa, 2019)
Soe hok gie as a literature student at the university of Indonesia played an active role in the struggle of the students of the 66th generation to overthrow the power of the old order led by president Soekarno. His harsh criticism reached several corners so that he was famous among students. An idealistic attitude and the use of harsh language are used to convey his aspirations. The students of the 1966 generation were indeed very strong and well-known for their actions at that time to voice TRITURA after the g 30s rebellion. The precarious situation at that time made students from various universities unite and hold demonstrations. This makes students considered in the national political map.